Deregulation of Retinaldehyde Dehydrogenase 2 Leads to Defective Angiogenic Function of Endothelial Colony–Forming Cells in Pediatric Moyamoya Disease. Issue 7 (July 2015) - Lee, Ji Yeoun; Moon, Youn Joo; Lee, Hae-Ock; Park, Ae-Kyung; Choi, Seung-Ah; Wang, Kyu-Chang; Han, Jung Woo; Joung, Je-Gun; Kang, Hyun Seung; Kim, Jeong Eun; Phi, Ji Hoon; Park, Woong-Yang; et al.
Abstract : Objective––: Moyamoya disease (MMD) is a common cause of childhood stroke, in which the abnormal function of the endothelial colony–forming cell (ECFC) plays a key role in the pathogenesis of the disease. This study was designed to identify genes involved in MMD pathogenesis using gene expression profiling and to understand the defective function of MMD ECFCs. Approach and Results––: We compared gene expression profiles of ECFCs isolated from patients with MMD and normal controls. Among the differentially expressed genes, we selected a gene with the most downregulated expression, retinaldehyde dehydrogenase 2 ( RALDH2 ). The activity of RALDH2 in MMD ECFCs was assessed by in vitro tube formation assay and in vivo Matrigel plug assay in the presence of all-trans retinoic acid. The transcriptional control of RALDH2 was tested using ChIP assays on acetyl-histone H3. In the results, MMD ECFCs inefficiently formed capillary tubes in vitro and capillaries in vivo, a defect restored by all-trans retinoic acid treatment. Knockdown of RALDH2 mRNA in normal ECFCs also induced decreased activity of capillary formation in vitro. The decreased level of RALDH2 mRNA in MMD ECFCs was attributed to defective acetyl-histone H3 binding to the promoter region. Conclusions––: From these results, we conclude that the expression of RALDH2 was epigenetically suppressed in ECFCs from patients with MMD, which may play a key role in their functional impairment. Abstract : Supplemental Digital Content is available in the text.